The Beauty of the Beast : Dierenkunst van oude en nieuwe meesters - Beele, Siska; De Cock, Marcel; De Vlieger-De Wilde, Koen; Depoorter, Matthias; Moens, Veerle; Van Hout, Nico (Bornem : Kasteel d'Ursel, 2017)
Creten, Johan ; Poncelet, Thierry ; Wastijn, Koen ; Coolen, Caroline ; Berchem, Nicolaes ; Delvoye, Wim ; Stobbaerts, Jan ; Verlat, Charles ; Vanmechelen, Koen ; Savery, Roelant ; Snijders, Frans ; Den Elzen, Mandy ; Verwee, Alfred ; Cornec, Jean-Luc ; Bellinkx, Ruben et al.
The Beauty of the Beast : Dierenkunst van oude en nieuwe meesters, Kasteel d'Ursel, Bornem, 25/05 - 15/10/2017
boek